Differences in local and systemic inflammatory markers in patients with obstructive airways disease - Tilemann, Lisa; Gindner, Lena; Meyer, Franz Joachim; Szecsenyi, Joachim; Schneider, Antonius (Primary care respiratory journal, 2011)
Asthma and chronic obstructive pulmonary disease (COPD) are characterised by airway and systemic inflammation, but little is known about differences and similarities in inflammatory markers in patients with obstructive airways disease.
Gesehen am 03.11.2022